Big data and smart aviation information management system - Xiangsheng Dou (Taylor & Francis Group, 2020)
Aviation industry is facing two major challenges of safety and performance improvement. They will be expected to be resolved in the context of big data. This paper focuses on the impact of big data on aviation industry and the construction of aviation big data platform and its information systems. Firstly, paper analyzes the relationship between big data and the development of smart aviation industry. Then, paper argues the basic ideas and framework for the construction of aviation big data platform and information system. Finally, paper proposes a multi-layer network correlation analysis method and applies it to analyze the spectrum and coupling degree of aviation big data information system. The research finds that aviation big data plays a very important role in the development of smart aviation industry, and the safety and performance of aircraft can be significantly improved through the construction of aviation big data information platform and information system, as well as the use of multilayer network correlation analysis methods. This paper provides ideas and countermeasures for the planning and construction of national aviation big data platform and information system, the construction of global aviation big data cooperation mechanism and the development of aviation big data technology.